The ASEAN Coordinating Centre for Humanitarian Assistance on Disaster Management (AHA Centre): Examining Gender-Based Approach in the 2018 Lombok Earthquake - Mardialina, Mala; Anam, Syaiful; Karjaya, Lalu Puttrawandi; Hidayat, Alfian; Lestari, Baiq Ulfa Septi (JAS (Journal of ASEAN Studies), 2024)
This research aimed to examine the role played by The ASEAN Coordinating Centre for Humanitarian Assistance on Disaster Management (AHA Centre) as the disaster coordination agency in the ASEAN region in addressing gender-based approach in Lombok earthquake disasters in 2018. The research utilized a qualitative descriptive research design. The findings indicate that the activities of the AHA Centre following the Lombok earthquake were predominantly focused on emergency response efforts and lacked significant involvement in gender-sensitive initiatives, ultimately yielding a dual impact on women. Through this research, it was ascertained that the suboptimal integration of gender perspectives in disaster management exacerbates the societal marginalization of women. The absence of gender-informed disaster management is evidenced by non-gender-disaggregated victim data, logistic aid provision overlooking gender-specific needs, as well as mitigation efforts and information dissemination disregarding gender dynamics. Thus, it emphasizes the lingering absence of a gender-responsive disaster management framework. This raises questions considering that ASEAN, including the AHA Centre, has already implemented a responsive gender declaration in 2015, whereas the AHA Centre has yet to demonstrate the establishment and implementation of a gender-based framework, due to inconsistencies in motivations towards universal norms. This study suggests that a masculine approach to disaster management hinders gender-sensitive disaster response efforts. It employs the concepts of gender mainstreaming and gender sensitivity to examine both the AHA Centre's disaster response efforts and the necessary steps to implement gender-sensitive disaster management. This research constructs the notion that disaster management efforts conducted without gender sensitivity, regardless of their quality, will not be optimal or effective.